Towards Smart and Sustainable Shopping Centres - A Response to The Challenges of Modern Supply Chains - Joanna MIKLINSKA (Communications of International Proceedings, 2022)
Although shopping centres have become a permanent feature in the landscape of many cities and are not only a place to do shopping but also to relax and meet friends, they have recently been affected by a number of problems. Changing societies following sustainable development, evolving shopping habits of final consumers who are more inclined to buy online, the development of new technologies and many others, give rise to new trends in supply chains and create many challenges for shopping centres today. These difficulties have been exacerbated by times of pandemic and lockdown, when centres were periodically closed and recorded losses. In response to this, various solutions are being implemented in shopping centres. However, the final effect of these measures, in such a turbulent environment, is difficult to determine. Therefore, the aim of this article is twofold: 1) to present the basic challenges in modern retail supply chains, and 2) to discuss solutions that are introduced to shopping centres in response to trends in supply chains, e.g. in Poland. In order to achieve the main objective of this article, the author analysed reference literature and reports on logistics solutions and trends in supply chains associated with retail (including shopping centres) as well as statistical data and recently published reports relating to the development of the shopping centre market in Poland, developed by the Polish Council of Shopping Centres as well as consulting institutions and real estate professionals.
Keywords: Shopping Centres; Supply Chain; Smart and Sustainable Shopping Centres